Assessing differences in the bioaccessibility of phenolics present in two wine by-products using an in-vitro model of fish digestion - Martínez-Antequera, Francisca P.; López-Ruiz, Rosalía; Martos-Sitcha, Juan Antonio; Mancera, Juan Miguel; Moyano, Francisco Javier (Frontiers in Veterinary Science, 2023)
Increasing attention is currently being paid to the protective role of polyphenols in health and oxidative status in fish. For this reason, the potential use of different natural sources of such compounds, like wine by products, is under study. One key step required to gain a better understanding on the biological roles of polyphenols for a given species is to assess the different factors affecting their digestive bioaccessibility, and a great number of such studies is based in the use of in vitro digestión models. In the present study the potential digestive bioavailability of the phenolic compounds present in wine bagasse and lees was evaluated for two different fish species. The two species showed great differences in their digestive phisyiology; the omnivorous gilthead sea bream (Sparus aurata) and the herbivorous flathead grey mullet (Mugil cephalus).The study was developed using in vitro models adapted to simulate their digestion and a factorial experimental design that simultaneously evaluated the effects of the ingredient used as source of polyphenols, presence or absence of feed matrix, fish species and digestion time. The release of the phenolic compounds was evaluated using ultra-high performance liquid chromatography (UHPLC) coupled to high resolution mass spectrometry (HRMS) detection. Both the presence of feed matrix and the type of wine by-product showed a significant effect on the digestive release of both total and specific types of polyphenols while fish species showed to be significant only for some specific compounds, like eriodyctiol or syringic acid. The time of digestion was not identified as a statistically significant factor in the release of phenolic compounds due to the great variability in the patterns observed that were classified as early, sustained and late. The present study is, to our knowledge, the first one on which an in vitro approach was applied to assess to what extent the possible complexation of wine polyphenols present in wine by-products with either digestive enzymes or components of the feed matrix could limit their bioaccessibility if included in diets of two different fish species.